Environmental supply chain management in the seafood industry: past, present and future approaches - Denham, Felicity; Howieson, J.; Solah, Vicky; Biswas, Wahidul (Elsevier, 2015)
This review discusses and analyses previous results in identification, development and implementation of cleaner production strategies within the seafood industry. The relevant peer reviewed articles were identified from a structured keyword search and analysed by both supply chain stage (capture and aquaculture, transport, processing, storage and retail), and examination of the cleaner production strategies implemented. Results found entities along the seafood supply chain generally worked separately to improve cleaner production processes and outputs to grow their own businesses. Whilst this approach can be beneficial, it ignores the broader cleaner production potential benefits gained when applied across multiple supply chain entities. The most effective cleaner production strategies for improved environmental performance in each sector of the supply chain were identified with the potential to reduce unnecessary handling, energy usage, storage costs and waste production. To ensure the greatest reduction in environmental impact, a whole of supply chain management system that incorporates life cycle assessment modelling is recommended.